KAJIAN TENTANG PERJANJIAN EKSTRADISI INDONESIA-MALAYSIA DALAM MEMBERANTAS KEJAHATAN DAN PELAKSANAANNYA DI INDONESIA - Rika Erawaty (Law Department, University of Widya Gama Mahakam Samarinda, 2011)
ABSTRACT Today ,Advances in technology and transportation are not only have a positive impact for the development of a country, but also a negative impact on their lives. With progress on the one hand it can provide for someone who wants to break away lawsuits. With the transportation advancement he could go to a single country to another country, mainly to neighboring countries which were located near to their home countries, which purpose is to break away lawsuits. For example Malaysia-Indonesia geographic and cultural factors might criminals to escape. Based on the background that the perceived need for a treatment between Indonesia and Malaysia regarding the transfer of criminals who fled. The agreement set forth in the form of Extradition Treatment, an agreement regarding the transfer of a person who has committed a criminal act to another country which is have right for judgment. The agreement stipulated in law No.9 of 1974, and this agreement has prompted Indonesia to ratify and develop national legislation on extradition, namely Law No. 1 of 1979.